Analisis Faktor Migrasi Pekerja Migran Indonesia Asal Blitar ke Luar Negeri Tahun 2010-2024 - Febiona Febiona; Fahrizal Taufiqqurachman; Moh. Saiful Anam (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study analyzes the factors influencing the migration of Indonesian Migrant Workers (PMI) from Blitar Regency to overseas destinations during the period 2010–2024, with a particular focus on the roles of poverty levels, the District Minimum Wage (UMK), and average years of schooling. The research employs a quantitative approach using a correlational method based on secondary time-series data, which are analyzed through multiple linear regression using EViews software. The estimation results indicate that the poverty level has a negative and statistically significant effect on the number of migrant workers, suggesting that extremely poor households face financial constraints that limit their ability to finance international migration processes. Meanwhile, the UMK and average years of schooling variables exhibit negative and positive coefficient directions, respectively, but are not statistically significant, indicating that increases in wages and education have not been able to directly restrain migration flows. Simultaneously, the three variables significantly affect PMI migration, with a coefficient of determination of 0.569. These findings demonstrate that labor migration decisions are multidimensional and influenced not only by economic factors but also by social and structural factors. The results support the push and pull theory of international labor migration, particularly in the context of semi-agrarian regions. Therefore, policies aimed at reducing forced migration should focus on strengthening local economic development, creating productive employment opportunities, and improving the quality of vocational education.